2016
DOI: 10.1021/acsnano.6b04110
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Production of High-Sensitivity, Label-Free DNA Biosensors Based on Back-Gated Graphene Field Effect Transistors

Abstract: Scalable production of all-electronic DNA biosensors with high sensitivity and selectivity is a critical enabling step for research and applications associated with detection of DNA hybridization. We have developed a scalable and very reproducible (>90% yield) fabrication process for label-free DNA biosensors based upon graphene field effect transistors (GFETs) functionalized with single-stranded probe DNA. The shift of the GFET sensor Dirac point voltage varied systematically with the concentration of target … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
151
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(163 citation statements)
references
References 26 publications
3
151
1
Order By: Relevance
“…Miniaturized chip-based electrical detection of DNA will eliminate the aforementioned limitations and would enable in-field or at home detection of specific DNA sequences and polymorphisms. [4] Significantly, electrical sensing-based methods have successfully lowered the limit of sequence specific DNA detection to the femtomolar level [5, 6] and thus should allow no need for PCR amplification of the genetic materials. A field effect transistor (FET) can be employed as a highly sensitive DNA sensor and can potentially be integrated with other on-chip analytical systems.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Miniaturized chip-based electrical detection of DNA will eliminate the aforementioned limitations and would enable in-field or at home detection of specific DNA sequences and polymorphisms. [4] Significantly, electrical sensing-based methods have successfully lowered the limit of sequence specific DNA detection to the femtomolar level [5, 6] and thus should allow no need for PCR amplification of the genetic materials. A field effect transistor (FET) can be employed as a highly sensitive DNA sensor and can potentially be integrated with other on-chip analytical systems.…”
mentioning
confidence: 99%
“…[6] Highly specific detection of biomolecules with relatively small electrical charges, such as DNA or RNA molecules, has been demonstrated recently. [9] Significantly, this study did not need any PCR-based or other amplification of the analytes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene demonstrates better sensitivity as its limit of detection is lower compared to carbon nanotubes for detection of analytes comprise of DNA, protein, small molecules and pathogens. (Viswanathan et al 2015) (Viswanathan et al 2015) (Mannoor et al 2014) (Ping et al 2015) (Feng et al 2011) (Ping et al 2015) (Ping et al 2016) (Guo et al 2011) (Xu et al 2014) (Ohno et al 2010) (Mao et al 2013) (Ohno et al 2010) (Mao et al 2013 (Lu et al 2009) (Nguyen et al 2011) (Kim et al 2009) (Star et al 2006) ) (Mao et al 2011) Recently, much efforts have been made to fabricate graphene based FET for DNA detection. In 2011, researchers from the University of California have fabricated graphene based FET for DNA detection.…”
Section: Graphene In Biosensorsmentioning
confidence: 99%
“…Surface area of chemically treated sensor was fully covered with single stranded probe DNA (Ping et al 2016) Zhang and Cui (2011) reported another approach in fabricating graphene based cancer biosensor for detection of prostate specific antigen (PSA) using layer-by-layer (LBL) self-assembly technique. The cancer sensor reported was fabricated on PET (Polyethylene terephthalate) flexible substrate with lithographic patterned gold electrodes.…”
Section: Graphene In Biosensorsmentioning
confidence: 99%